Out-of-equilibrium 2D Ising spin glass: almost, but not quite, a free-field theory. (23rd October 2018) - Fernandez, L A; Marinari, E; Martin-Mayor, V; Parisi, G; Ruiz-Lorenzo, J J
Abstract: We consider the spatial correlation function of two-dimensional Ising spin glass under out-of-equilibrium conditions. We pay special attention to the scaling limit reached upon approaching zero temperature. The field-theory of a non-interacting field makes a surprisingly good job of describing the spatial shape of the correlation function of the out-of-equilibrium Edwards–Anderson Ising model in two dimensions.